Pelatihan Pembuatan Jebakan Hama dan Pestisida Nabati untuk Mengatasi Hama di Kebun Gizi Kelompok PKK Desa Anyar - Armiani, Sucika; Harisanti, Baiq Muli; Dharmawibawa, Iwan Doddy; Hajiriah, Titi Laily; Mursali, Saidil (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to enhance the knowledge and skills of the community in producing insect traps and botanical pesticides, identifying plant species with potential as botanical pesticides, and applying both technologies to reduce the use of chemical pesticides in the nutrition garden program of Anyar Village. The target participants were members of the Anyar Village PKK group, particularly those in Working Group 3 (Pokja 3) who are responsible for implementing the nutrition garden program. The activity consisted of four stages: coordination, socialization, training, and evaluation. Socialization was carried out through lectures explaining the basic concepts and practical steps in producing botanical pesticides. The training was conducted through direct practice, including the creation of insect traps made from yellow adhesive plastic bottles and the preparation of botanical pesticides using neem leaves (Azadirachta indica), lemongrass (Cymbopogon citratus), galangal (Alpinia galanga), and soursop leaves (Annona muricata L.), mixed with water and dish soap as an adhesive agent. A total of 17 participants attended the activity. Achievement of the program objectives was evaluated through participant response surveys using questionnaires, and the data were analyzed descriptively. The evaluation results showed that 100% of participants understood the material and were able to independently prepare botanical pesticides, while 95% indicated a commitment to applying botanical pesticides in the nutrition garden activities.